ANALYSIS OF CONSUMER PREFERENCES AND TRAVEL BEHAVIOR IN JAKARTA'S TOURISM DISTRICTS TO HELP MAKE PROMOTIONAL PROGRAMS - Maria Ulfah Catur Afriasih; Muhamad Ridwan (Jurnal Ilmiah Publipreneur, 2022)
Domestic travelers, also known as local tourists, made 603.2 million trips in 2021, according to the Central Statistics Agency (BPS). This figure grew from the previous year, when it was up 14.95 percent from 524.57 million trips. This research aims to examine Jakarta Tourist's preferences and customer behavior as part of attempts to develop a more successful tourism marketing strategy. It is also an attempt to understand market characteristics and desires in order to become a significant reference in the marketing of cultural tourist goods and the development of promotional programs. A field survey was done in Jakarta to aid in the implementation of the analysis and get the best possible findings. The sample approach utilized in this study was non-probability sampling using the online survey method since the data collection technique employed online questionnaires with the aid of Google Forms utilizing the self-administrated questionnaire method. Online surveys are conducted with uncontrolled distribution, meaning that the questionnaire can be completed by anybody, anywhere. The screening questions in the questionnaire, however, decide whether the responder is included in the sample. With a total score of 856, the top five consumer preferences for picking the most popular tourist locations include tourist attractions with plenty of rides, utilizing air transportation, going on culinary excursions, and staying at hotels Keyword: consumen preferences, consumer behaviour, local tourism